Experience and Expectations of Muslim Gender Roles in the Baltics: The "Subaltern" Voices in the Face of Public Discourse - Balode, Dace (Religion and society in Central and Eastern Europe, 2023)
Women of Muslim background living in the Baltics, like others, are often confronted with images of perceived gender roles in Muslim communities and societies. But they, unlike non-Muslims, have their own take on these images, partially stemming from their personal experiences and religious convictions but also as responses, sometimes unrealised, to the public discourse. Through their narrations, these women, using their own examples, apparently seek to deconstruct the images of gender relations among Muslims. On the other hand, it is mainly through mass media that ordinary citizens become familiarised with the cultural traditions and habits of distant societies. In the Baltics, much of the reporting on Muslim societies and cultures is conducted by journalists who often lack an informedunderstanding of the complex realities of the societies they report on. Reports on sensitive issues, such as gender relations and sexuality among Muslims, are especially in demand. Based on in-depth interviews, the present paper shows the plethora of positions women of Muslim background living in the Baltics can hold related to Islam and gender roles and compares how their positions oppose or conform to the images held in the public and recycled in the media.